2016
DOI: 10.1586/17474086.2016.1136209
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Glucose Metabolism in Thalassemia Major: An Update

Abstract: In patients with TM, uncontrolled iron overload has serious clinical consequences with considerable morbidity and mortality. Complications include liver damage, cardiac disease and endocrine dysfunction. Diabetes is an important complication of TM. The mechanisms of abnormal glucose homeostasis are complex and multifactorial. This review updates the current knowledge about glycemic abnormalities in TM patients and directs the attention to an early diagnosis and proper management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…We found that subjects with thalassemia who had low Mt/N had insulin resistance by both of these indices. Since Mt/N increased with age in our study, as does the prevalence of impaired glucose tolerance (42), this inverse correlation was unexpected. However, adults with metabolic syndrome with insulin resistance were reported to have lower mitochondrial content in leukocytes (17).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…We found that subjects with thalassemia who had low Mt/N had insulin resistance by both of these indices. Since Mt/N increased with age in our study, as does the prevalence of impaired glucose tolerance (42), this inverse correlation was unexpected. However, adults with metabolic syndrome with insulin resistance were reported to have lower mitochondrial content in leukocytes (17).…”
Section: Discussionsupporting
confidence: 43%
“…Iron overload in thalassemia is associated with early occurrence of insulin resistance with subsequent pancreatic damage and insulin deficiency leading to diabetes mellitus (42). HOMA-IR is a measure of hepatocyte sensitivity to insulin in the fasting state, while ISI measures whole-body insulin sensitivity following a glucose load (43).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mild disorders are usually asymptomatic; impaired glucose tolerance (IGT) is common, occurring in up to 24.1%. [8][9][10][11] Unfortunately, this represents an additional potential risk to their cardiac function. [12] Although iron overload induced DM shares certain characteristics with both type 1 diabetes and type 2 diabetes, it appears to be a separate entity with a unique pathophysiology.…”
Section: Glucose Abnormalities In Patients With Thalassemia Majormentioning
confidence: 99%
“…Therefore, patients with TM and health professionals should be aware of the high incidence of glucose abnormalities in patients with thalassemia syndromes 5,7. Detecting the pre-diabetes stage is critical because prediabetes and clinical diabetes can potentially be reversed or prevented with optimum chelation treatment 5,7…”
Section: Introductionmentioning
confidence: 99%
“…Detecting the pre-diabetes stage is critical because prediabetes and clinical diabetes can potentially be reversed or prevented with optimum chelation treatment 5,7…”
Section: Introductionmentioning
confidence: 99%